Postawa trenera wobec filozofii karate i jego system wartości, a postawy i systemy wartości jego uczniów = The attitude of the coach to the philosophy of karate and his system of values and attitudes and value systems of its students - Zienowicz, Aleksandra; Parzelski, Dariusz; Budnik-Przybylska, Dagmara (Journal of Education, Health and Sport, 2015)
Zienowicz Aleksandra, Parzelski Dariusz, Budnik-Przybylska Dagmara. Postawa trenera wobec filozofii karate i jego system wartości, a postawy i systemy wartości jego uczniów = The attitude of the coach to the philosophy of karate and his system of values and attitudes and value systems of its students. Journal of Education, Health and Sport. 2015;5(9):149-169. ISSN 2391-8306. DOI10.5281/zenodo.30280 http://dx.doi.org/10.5281/zenodo.30280 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A149-169 https://pbn.nauka.gov.pl/works/617848 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.07.2015. Revised 24.08.2015. Accepted: 29.08.2015. Postawa trenera wobec filozofii karate i jego system wartości, a postawy i systemy wartości jego uczniów The attitude of the coach to the philosophy of karate and his system of values and attitudes and value systems of its students Aleksandra Zienowicz (1), Dariusz Parzelski (1), Dagmara Budnik‑Przybylska (2) (1) Uniwersytet SWPS Warszawa (2) Uniwersytet Gdański „O ile rozwój fizyczny jest początkiem karate, o tyle rozwój duchowy jest celem ostatecznym tej sztuki walki.” Sosai Masutatsu Oyama Streszczenie Wprowadzenie: Problematyka utrzymania równowagi między życiem osobistym a zawodowym, pęd społeczeństwa, nastawienie na „mieć” (por. Gałkowska-Jakubik, 2007) skłania do refleksji na temat roli systemów wartości w życiu człowieka (Matusewicz, 1975). Punktem wyjścia były założenia filozofii karate oraz komercjalizacja tej sztuki walki, która wyłania dwa style: sportowy, skupiony na wyniku, sukcesie oraz styl tradycyjny, który koncentruje się na utrzymywaniu równowagi psychofizycznej, rozwoju duchowym prowadzącym do doskonałości moralnej (Miłkowski, 1983, Budnik, 2005). Cel pracy: Celem przedstawionego badania jest eksploracja systemów wartości trenerów oraz ich uczniów, z uwzględnieniem opinii uczniów na temat swoich wychowawców, w oparciu o praktykowany styl. Materiał i metoda: Uczestnikami badania było 22 trenerów oraz 54 uczniów karate. Analiza wyników skali, stworzonej na potrzeby badania, postawa wobec filozofii (PwF), wyłoniła 11 trenerów, 35 uczniów „sportowych” oraz 11 trenerów, 19 uczniów „tradycjonalistów”. Badanie przeprowadzono wykorzystując skalę wartości schelerowskich (Brzozowski, 1995) Wyniki: Zgodnie z założeniami trenerzy i uczniowie “tradycjonaliści” uzyskali wyższe wyniki na skali wartości moralnych oraz podskali czynnikowej świętości religijnych Wnioski: „Tradycjonaliści” kierują się ascetycznym wzorem edukacyjnym, który zakłada, że poprzez rozwój fizyczny oraz duchowy dąży się do doskonałości moralnej. Wartości wynikające z duchowości stanowią nierozłączny element dobrego życia. Słowa kluczowe: karate, wartości, trener-uczeń. Abstract Introduction: The issue of maintaining the balance between personal and professional lives, society ofrush, the attitude to "be" (cf.. Gałkowska Jakubik, 2007) invites us to reflection concerning the role of systems of values in human life (Matusewicz, 1975). The starting point was philosophy of karate and commercialization of this martial art that emerges two styles: sporty, focused on the outcome, success and traditional style, which focuses on maintaining balance of mental and physical, spiritual development leading to moral perfection (Miłkowski, 1983, Budnik, 2005 ). Aim: The aim of this study is to explore the trainers’ systems of values and their students, including students’ opinion about their teachers, based on the practiced style. Material and Methods: The participants of the study were 22 coaches and 54 karate adepts. The study was conducted by using a scale of Scheler’s values (Brzozowski, 1995) Results: ’Traditionalists’ trainers and students scored higher on the scale of moral values and religious sanctity factor subscale Conclusion: "Traditionalists" are guided by ascetic educational model, which assumes that through the t physical and spiritual development they seek to moral perfection. The values resulting from spirituality are an inseparable part of the good life. Keywords: karate, values, trainer-student.